DESCRIPTION OF THE HISTORY OF RELIGIONS AND WORSHIP CEREMONIES IN THE WORKS OF ABU RAYHAN BERUNI (Sciental Journal of Education Humanities and Social Sciences, 2025)
As an encyclopedic scholar, Beruni wrote many works. In his works on the history of religions, he covered the emergence of Christianity, its councils (cathedrals), worship ceremonies, holy books, and conflicts between Christian movements. He also has thoughts about Saint Paul, who inherited the Christian traditions that emerged thousands of years ago. The article analyzes Beruni's views on Christianity.